IMPROVING STUDENTS’ ACTIVENESS IN SPEAKING USING FLASHCARDS - Suharta, Yovita; Sada, Clarry; Sutapa, Gatot (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is aimed at improving students’ speaking activeness using flashcards media in teaching learning process. The subject of this research is class VIII C students at SMP Kemala Bhyangkari Sungai Raya in academic year 2017/2018. This research was done by asking and answering the materials to make the students active in speaking. In this research, the researcher implemented flashcards as the media. Therefore, the method used in this research is a classroom action research in which the researcher concerned with the improvement of students’ activeness in every meeting. This research was conducted in two cycles. In collecting the data the researcher observed the improvement of students’ activeness in speaking through observation checklist, field notes, and activeness table. The result of this research showed that flashcards media can improve the students’ activeness in speaking by asking and answering the materials. The students’ individual score in activeness also improved in teaching learning process. From the result, it can be concluded that students’ activeness in speaking by asking and answering the materials taught by flashcards media was improved. In addition, this media can help students to speak actively.                          Keywords: Flashcards, Speaking Activeness, Classroom Action Research.